MORPHOLOGICAL STUDIES ON GRAM POD BORER, HELICOVERPA ARMIGERA (HUBNER) (LEPIDOPTERA : NOCUTIDAE) - SHARMA, S.P.; GOEL, S.C..; SAINI, M. L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
The head capsule width of Helicoverpa armigera (Hb) larvae falls into six groups, each of which could be considered an instar. In addition to the head capsule width, an increase in the length and width of otherhead and body appendages also followed a geometrical progression confirmity with Dyar's law.